Safety Parameters of Quantum Molecular Resonance Devices During Thyroid Surgery: Porcine Model Using Continuous Neuromonitoring - Tseng, Hsin-Yi; Huang, Tzu-Yen; Lin, Yi-Chu; Wang, Jia Joanna; Ko, How-Yun; Chuang, Cheng-Hsun; Lu, I-Cheng; Chang, Pi-Ying; Randolph, Gregory W.; Dionigi, Gianlorenzo; Chang, Ning-Chia; Wu, Che-Wei (Frontiers in Endocrinology, 2022)
Objectives: Quantum molecular resonance (QMR) devices have been applied as energy-based devices in many head and neck surgeries; however, research on their use in thyroid surgery is lacking. This study aimed to investigate the safety parameters of QMR devices during thyroidectomy when dissection was adjacent to the recurrent laryngeal nerve (RLN). Methods: This study included eight piglets with 16 RLNs, and real-time electromyography (EMG) signals were obtained from continuous intraoperative neuromonitoring (C-IONM). QMR bipolar scissor (BS) and monopolar unit (MU) were tested for safety parameters. In the activation study, QMR devices were activated at varying distances from the RLN. In the cooling study, QMR devices were cooled for varying time intervals, with or without muscle touch maneuver (MTM) before contacting with the RLN. Results: In the activation study, no adverse EMG change occurred when QMR BS and MU were activated at distances of 2 mm or longer from the RLNs. In the cooling study, no adverse EMG change occurred when QMR BS and MU were cooled in 2-second intervals or immediately after MTM. Conclusion: QMR devices should be carefully used when performing RLN dissection during thyroid surgery. According to the activation and cooling safety parameters in this study, surgeons can avoid RLN injury by following standard procedures when using QMR devices.